Luminescence and photocatalytic studies of Sm3+ ion doped SnO2 nanoparticles - Singh, L. P.; Luwang, Meitram Niraj; Srivastava, S. K. (New Journal of Chemistry, 2014)
Sm3+ ion doped tetragonal SnO2 nanoparticles have been synthesized by the polyol method and its concentration and annealing effects on photoluminescence properties are studied. The XRD results show the changes of lattice parameters with the incorporation of the Sm3+ ion into the SnO2 host lattices. Fourier transform infrared (FTIR) data indicate the formation of a Sn-O bond and capping of the nanoparticles by ethylene glycol. The broad emission peaks observed around 350 to 550 nm are attributed to the emission from defects or traps present in the host SnO2. The typical emission peaks of the Sm3+ ion are observed and there is efficient energy transfer between the host, SnO2 and the dopant, Sm3+ ion. Further, the prepared samples are experimented towards the photocatalytic behavior on selected triphenylmethane dyes, Ethyl Violet (EV) and Brilliant Green (BG). The degradation of dyes was found to be enhancing in the presence of Sm3+ ions as it suppress the e e(CB)(-) and h(VB)(+) recombination.